The Chronology of the Levantine Middle Palaeolithic Period in Retrospect - Ofer Bar-Yosef; Liliane Meignen (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
During the last 20 years, in the context of new interdisciplinary research projects in the Near East, significant changes have emerged in our ideas about the origin and early evolution of Modern Humans. Most of these changes are the result of the development and application of dating techniques such as TL and ESR but no less have the advent of lithic technological studies contributed refinements in the classical tripartite scheme of the Levantine Middle Palaeolithic. The aim of this paper is to explore in retrospect the various proposals for dating the archaeological deposits in which human fossils have been recovered. New hypotheses based on the recent dating are presented radiometric ignoring certain ambiguities.